HBR guide to emotional intelligence (Harvard Business Review Press, 2017)
Research by Daniel Goleman, a psychologist and coauthor of Primal Leadership, has shown that emotional intelligence is a more powerful determinant of good leadership than technical competence, IQ, or vision. Influencing those around us and supporting our own well-being requires us to be self-aware, know when and how to regulate our emotional reactions, and understand the emotional responses of those around us. No wonder emotional intelligence has become one of the crucial criteria in hiring and promotion. But luckily it's not just an innate trait: Emotional intelligence is composed of skills that all of us can learn and improve on. In this guide, you'll learn how to: *Determine your emotional intelligence strengths and weaknesses *Understand and manage your emotional reactions *Deal with difficult people *Make smarter decisions *Bounce back from tough times *Help your team develop emotional intelligence. Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.